PERAN YAYASAN PELAYANAN PEKABARAN INJIL INDONESIA (YPPII) BATU DALAM PENGELOLAAN DANA DAN ASSET SOSIAL KEAGAMAAN BAGI PEMBERDAYAAN UMAT BERAGAMA - Agus Mulyono (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
The area managed by YPPII Batu in funding management and religious social assets includes education area, diaconal service and orphanage care. The establishment of YPPII foundation was inspired by the many children who suffer from the violence. The case of Poso led to ± 20 thousand children loset their parents and their future, and so YPPII takes care of some children of Poso riot victims. This study used a qualitative approach in the form of descriptive case studies. Qualitative research emphasizes the researcher as the main instrument of the data collection and analysis.